Pemanfaatan Maggot Sebagai Pakan Lele Dan Pengolah Limbah Sampah Organik - Roni Salambue; Muhammad Izzudin; Nanda Nur Fitriadi; Muhammad Yusuf Alen; Silvia Agusti; Musdalifah Musdalifah; Sri Nurhidayati; Cinta Fitria; Dedes Nawati (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Bukit Payung Village is a village in Bangkinang District, Kampar Regency which was formed in 1986 from the Trans SP 3 SKP A Bangkinang program from the Transmigration Department of Kampar Regency. The Bukit Payung Village Youth Organization has become a catfish farming business. Feed costs are the largest component in catfish farming activities. Commercial feed produced by factories has guaranteed quality and quantity, but the problem is that the price of feed produced by factories is getting more expensive day by day, so alternative feeds are needed to reduce costs. One alternative fish food is maggot or Hermetia illucens. Maggots are organisms that originate from black soldier eggs which are known as rotting organisms because of their habit of consuming organic materials. Maggots consume organic materials to grow and reproduce, this makes maggots one of the natural organic waste processors.